USAHA-USAHA PENGUATAN PERAN DAN FUNGSI KECAMATAN DI ERA OTONOMI DAERAH - Mugito, Mr. (Jurnal Ilmiah Administrasi Publik, 2012)
Kecamatan is a subordination regent government, which have function to be following decisive for realization goals of local autonomous at Indonesia.Â  Now, kecamatan still not do optimalization roles and functions. Mintsberg (1979 : 181), says that âOnce the units have been designed, it seems appropriate to address the question of how much power each should have.â This konsep will be made as basic for answer problem in this peper. Those problem need accomplishment, so that organization unit can support acceleration to realizatios that goal. In this peper try to clarify much attempt so kecamatan can optimal to realization its role and function